COSTS OF TRAINING NURSES IN THE INSERTION, REVISION, AND REMOVAL OF INTRAUTERINE DEVICES - Juliana da Silva Nogueira; Karla Romana Ferreira de Souza; Evelyn da Silva Ferreira Lins; Elizandra Cassia da Silva Oliveira; Edgard Leonardo Nery Meira Lima; Adriana Falangola Benjamin Bezerra (Universidade Federal do Paraná, 2024)
Objective: To analyze the costs of training in reproductive planning, with nurses' insertion, revision, and removal of intrauterine devices. Method: Case study, with data collected between May and December 2022, in Recife, Pernambuco, Brazil. The micro-costing evaluation was carried out using absorption costing. Results: Data from five classes in 2022 were analyzed, totaling 70 nurses, and the expenses and direct and indirect costs of offering the course were identified. The cost per class was R$17,846.89/U$3,307.79), with an average of R$1,820.38 or U$337.39/student/edition. Compared to other similar courses, it is considered a low-cost course with promising results for the quality of sexual and reproductive health care. Conclusion: Investing in training nurses in reproductive planning helps to reduce the indicators of maternal and child morbidity and mortality associated with unplanned pregnancies.